2015
DOI: 10.3389/fncel.2015.00407
|View full text |Cite
|
Sign up to set email alerts
|

X MARCKS the spot: myristoylated alanine-rich C kinase substrate in neuronal function and disease

Abstract: Intracellular protein-protein interactions are dynamic events requiring tightly regulated spatial and temporal checkpoints. But how are these spatial and temporal cues integrated to produce highly specific molecular response patterns? A helpful analogy to this process is that of a cellular map, one based on the fleeting localization and activity of various coordinating proteins that direct a wide array of interactions between key molecules. One such protein, myristoylated alanine-rich C-kinase substrate (MARCK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 97 publications
(160 reference statements)
1
62
0
1
Order By: Relevance
“…Proteins affected by CYP46A1 activation and Cyp46a1 ablation were also different, except CTNND2, DPYSL2, GAP43, MAP1B, MAP6, MARCKS, PKP4, and SAMD14 ( Fig. 6B), which all pertain to neurite growth excluding SAMD14 (122)(123)(124)(125)(126)(127).…”
Section: Brain Phosphoproteomementioning
confidence: 99%
“…Proteins affected by CYP46A1 activation and Cyp46a1 ablation were also different, except CTNND2, DPYSL2, GAP43, MAP1B, MAP6, MARCKS, PKP4, and SAMD14 ( Fig. 6B), which all pertain to neurite growth excluding SAMD14 (122)(123)(124)(125)(126)(127).…”
Section: Brain Phosphoproteomementioning
confidence: 99%
“…It has since become one of the most robust and well characterized read-outs of conventional and novel PKC signaling [49]. Its deletion in mice has revealed that it is required for mouse brain development and postnatal survival [50].…”
Section: Regulation Of the Cytoskeleton: Marcks Gap43 And Taumentioning
confidence: 99%
“…PKC has also been linked to N-methyl-d-aspartate receptor (NMDAR)-mediated reduction in tau phosphorylation [69]. Overall, PKC's regulation of cytoskeleton dynamics in the brain plays a critical role not only in synapse formation and maintenance, but also in the functions of non-neuronal cells such as endothelial and glial cells [49].…”
Section: Regulation Of the Cytoskeleton: Marcks Gap43 And Taumentioning
confidence: 99%
“…However, MeHg exposure elicited a biphasic increase in MARCKS phosphorylation, and significant differences were observed at concentrations higher than 0.3 µ M at 24 hr after the treatment. Since the interactions between MARCKS and its target molecules, such as actin and phosphatidylinositol 4,5-bisphosphate, are regulated by phosphorylation at the effector domain of MARCKS [3, 17], it is likely that the phosphorylation of MARCKS induced by MeHg is directly involved in the MeHg toxicity on EA.hy926 cells. MeHg is known to induce reactive oxygen species (ROS) production, including hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous mutant mice with targeted deletion of the Marcks gene showed morphological abnormalities in the central nervous system and perinatal death [39], suggesting the essential role of MARCKS in brain development. MARCKS plays roles in cellular functions, such as adhesion, migration, proliferation and fusion in multiple types of cells through its interaction with the membrane phospholipids and actin, which is regulated by phosphorylation at the central polybasic region of MARCKS called the effector domain [2, 3, 27, 48]. In vascular smooth muscle and endothelial cells, MARCKS has been shown to regulate proliferation [46], cell migration [17, 26, 47] and endothelial cell permeability [16].…”
mentioning
confidence: 99%